Creating mosaics: The interrelationships between knowledge and context. - Barbara J. Daley (Adult Education Research Conference, 1997)
This qualitative study analyzed the interrelationships between knowledge gained in continuing education programs and the context in which professionals practice. Findings indicate that the process of constructing a knowledge base was affected by the structural, human resources, political and symbolic frames of the context of practice.